Impact of Urbanization on Health and Well-Being in Ghana. Status of Research, Intervention Strategies and Future Directions: A Rapid Review - Doris Akosua Tay; Reginald T. A. Ocansey (Frontiers Media S.A., 2022)
IntroductionGhana like other African countries is facing multiple health threats due to expansion of urban populations. Globally, the urbanization phenomenon has received considerable attention and modest steps have been undertaken to address it. Ghana is stalling on implementation of policies and interventions targeted at alleviating the menace.ObjectivesThis review examined research evidence, interventions, and policies relating to urbanization and threats to health and well-being of people living in Ghana. The review focused on three areas including urbanization threats to health and well-being, health risks associated with urbanization, and interventions and policies.Materials and MethodsThe search spanned from year 2000 to February 2022 covering documents related to urbanization, health, and well-being. Databases used for the search include African Journals Online, Annual Reviews (Biomedical, Life & Physical sciences, Social Sciences), BioMedCentral, BioOne, BLDS digital library, Cambridge University Press, ClinicalKey, CINAHL, University of Ghana Digital Collections/UGSpace, JSTOR, Medline and Wiley Online Library.ResultsEnvironmental risk factors, urban planning, water-related, behavior-related, and socioeconomic factors were important urbanization threats to health and well-being. Health risks identified include airborne diseases, waterborne diseases, malaria, and non-communicable diseases such as hypertension and lung cancer. Additionally, there is evidence of non-implementation and/or non-enforcement of existing interventions and policies.Conclusion and RecommendationEvidence from this rapid review shows that urbanization impacts on health and well-being of people in Ghana. Urbanization threats that expose populations to health risks could be reduced through commitment to implementation, surveillance and monitoring of policies and interventions. Communities and individuals must be equipped to take control of their health and well-being.